Cryotherapy for Actinic Keratosis: Basic Principles and Literature Review - Arisi M; Guasco Pisani E; Calzavara-Pinton P; Zane C (Dove Medical Press, 2022)
Mariachiara Arisi, Edoardo Guasco Pisani, Piergiacomo Calzavara-Pinton, Cristina Zane Department of Dermatology, University of Brescia, ASST Spedali Civili di Brescia, Brescia, ItalyCorrespondence: Mariachiara Arisi, Department of Dermatology, University of Brescia, ASST Spedali Civili di Brescia, P.le Spedali Civili 1, Brescia, 25123, Italy, Tel +390303995300, Fax +390303995015, Email mariachiara.arisi@gmail.comAbstract: Actinic keratoses (AKs) are pre-malignant epithelial lesions induced by chronic cumulative UV exposure. Several guidelines concerning AKs treatment have been published in the past years. Among destructive procedures, cryotherapy is today considered a standard first-line approach in case of single lesions. The aim of the present review article is to analyse the treatment technique, its efficacy and safety.Keywords: cryotherapy, cryosurgery, actinic keratosis, treatment